False-Positive Results in a Recombinant Severe Acute Respiratory Syndrome-Associated Coronavirus (SARS-CoV) Nucleocapsid Enzyme-Linked Immunosorbent Assay Due to HCoV-OC43 and HCoV-229E Rectified by Western Blotting with Recombinant SARS-CoV Spike Polypeptide - Woo, Patrick C. Y. (American Society for Microbiology, 2004)
Using paired serum samples obtained from patients with illness associated with increases in anti-human coronavirus OC43 (HCoV-OC43) or anti-HCoV-229E antibodies, we examined the possibility of false-positive results detected in a recombinant severe acute respiratory syndrome (SARS)-associated coronavirus (SARS-CoV) nucleocapsid protein immunoglobulin G enzyme-linked immunosorbent assay (ELISA). Three of the 21 and 1 of the 7 convalescent-phase serum samples from persons with increases in antibodies against HCoV-OC43 and HCoV-229E, respectively, tested positive by the recombinant SARS-CoV nucleocapsid protein-based ELISA. None of these samples were found to contain a specific antibody in the recombinant SARS-CoV spike polypeptide-based Western blot assay.